Chemical constituents of three Malaysian Ancnonaceae - Rozana,; Mazdida, S.; Shasya, U.; Awang, K.; Hamid A. Hadi, A. (Malaysian Journal of Science, 1999)
Three Malaysian Annonaceous climbers plants, Cyathostemma viridiflorum Griff., Desmos dumosus and Fissistigma manubriatum, have been studied for their studied for their chemical constituents. The plants afforded seven alkaloids and one chalcone. Cythostemma viridiflorum yielded three oxoaporphine which are liriodenine, lanuginosine and atherospermidine, and an aporphine, anonaine. Desmos dumosus gave three alkaloids of which two are of the oxoaporphine type; o-methylmoschatoline and lysicamine, and a tetrahydroprotoberberine, discretamine. Fissistigma manubriatum afforded three oxoapoiphines: lanuginosine, lysicamine and liriodenine. The chalcone isolated was a,2'-dihydroxyÂ3 ',4',5'-trimethoxychalcone. Structural elucidation were carried out by UV, IR, MS and IHNMR.